Penyuluhan Mengenai Pertolongan Pertama pada Kecelakaan (P3K) bagi Calon Pendonor Darah - Dahniar Dahniar; A. Arviani Desianti Nur (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Blood donation is a humanitarian activity that benefits patients in need of a blood transfusion. However, the process of donating blood can also pose health risks to donors, especially if they are not in optimal condition or lack knowledge of proper first aid measures. Most blood donors experience mild side effects such as dizziness, weakness, or nausea, while in certain cases, more serious reactions like fainting or bleeding at the needle insertion site may occur. Therefore, understanding First Aid in Accidents (P3K) is essential for prospective blood donors so they can prevent, recognize, and properly manage these side effects. Based on this, an educational outreach program has been conducted for the community of Tamparang Keke Subdistrict, Mamajang District, Makassar City. This outreach program aims to enhance basic knowledge among community members who wish to donate blood regularly.